Pengaruh Brand Ambassador Aktor Korea Terhadap Brand Image Produk Scarlett (Studi Kasus Mahasiswa Universitas Tidar): Studi Kasus Mahasiswa Universitas Tidar - Sofiyah nurul Hakimah; Budi Hartono (CV ODIS, 2022)
Marketing strategy involving brand ambassadors is one way for companies to improve their brand image. This research was conducted to analyze how influential the brand ambassador was on the brand image of Scarlett products for Tidar University students. This research is a type of quantitative research with multiple linear regression analysis, normality test, correlation analysis, coefficient of determination, and hypothesis testing (t-test). The population in this study were Tidar University students with a total sample of 50 respondents. The sample was determined using a non-probability sampling technique, the type of purposive sampling. The data were analyzed using the SPSS 26 application. From the results of hypothesis testing, it was found that only the power indicator affected the brand image (t-value 2,943 > t-table 2,228). Meanwhile, indicators of visibility (t-value -500 < t-table 2,228), credibility (t-value 1,717 < t-table 2,228), and attraction (t-value -1,099 < t-table 2,228) do not affect brand image. The analysis of the coefficient of determination showed the results of 0.380